2008
DOI: 10.1111/j.1365-246x.2008.03946.x
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic evidence of slab detachment beneath eastern Turkey and the Caucasus

Abstract: SUMMARY Teleseismic phase readings from the Eastern Turkey Seismic Experiment (ETSE) have been inverted using teleseismic tomography in order to create a 3‐D image of the underlying mantle beneath Eastern Turkey. The aim was to investigate the existence of an upper mantle negative velocity anomaly that is used to explain the uplift of Eastern Anatolian plateau and the potential pieces of detached oceanic slabs related to Neo‐Tethyan subduction suggested by previous studies. Using teleseismic waveforms from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 44 publications
8
101
0
2
Order By: Relevance
“…Recently, tomography studies by Biryol et al (2011) andFichtner et al (2013a) have confirmed that a hot and buoyant asthenospheric body supports the ∼ 2 km elevation of the Eastern Anatolian Plateau in the presence of an about 45 km thick crust (Şengör et al, 2003;Zor et al, 2003). At about 350 km depth, a fast anomaly has been found by tomographic studies and interpreted to represent a slab detachment (Lei and Zhao, 2007;Zor, 2008 Kalafat et al, 2008), NOA-Net, Aristotle University Thessaloniki (HT-Net) and GEOFON (Hanka and Kind, 1994;GEOFON Data Centre, 1993). We apply the S-receiver function method to this data set in order to image seismic discontinuities in the crust and upper mantle.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, tomography studies by Biryol et al (2011) andFichtner et al (2013a) have confirmed that a hot and buoyant asthenospheric body supports the ∼ 2 km elevation of the Eastern Anatolian Plateau in the presence of an about 45 km thick crust (Şengör et al, 2003;Zor et al, 2003). At about 350 km depth, a fast anomaly has been found by tomographic studies and interpreted to represent a slab detachment (Lei and Zhao, 2007;Zor, 2008 Kalafat et al, 2008), NOA-Net, Aristotle University Thessaloniki (HT-Net) and GEOFON (Hanka and Kind, 1994;GEOFON Data Centre, 1993). We apply the S-receiver function method to this data set in order to image seismic discontinuities in the crust and upper mantle.…”
Section: Introductionmentioning
confidence: 91%
“…Paleomagnetic directions in the west Anatolian extensional province are rotated clockwise [Piper et al, 2008], which we attribute to rotations associated with extension. The plate thickness in the east Anatolian contractional province is 40-50 km [Zor, 2008], in the central Anatolian Ova province 36-40 km thinning toward the southern edge [Zor, 2008], and in the west Anatolian extensional province spot thicknesses are generally in the range of 22-30 km [Tirel et al, 2004;Zhu et al, 2005], with a thickness of only 8 km in the Sea of Marmara [Bécel et al, 2009]. We assume that the thickness of the plate in the central Anatolian Ova province is approximately that of the whole region prior to the present tectonic regime (i.e., at least 13 Ma.).…”
Section: Driving Forcesmentioning
confidence: 99%
“…By checking regional waves in the crust (L g ) and the upper mantle (S n ), they observed both waves disappearing through the Eastern Anatolian Plateau, coinciding with the zones of inefficient S n propagation, and heating of a thin to absent mantle. Zor's (2008) tomographic results showed that the negative velocity anomaly above the slab-like positive anomaly may be an upwelling hot asthenosphere in the upper mantle beneath Eastern Anatolia and brings about slow shear-wave velocity anomalies. A magnetotelluric study carried out in Eastern Anatolia by Türkoğlu et al (2008) showed that the upper mantle has a very low resistivity, which is related to the presence of shallow and partially molten material.…”
Section: Station Pairs (Vanb-kopr Vanb-mlaz Vanb-karo Svan-cldr Gmentioning
confidence: 99%
“…A vast volume of the volcanic activity in the Eastern Anatolia (~43,000 km 2 ) was produced after regional block uplift (11-13 Ma) and this process moved from the north in the Erzurum-Kars Plateau to the south-southeast in the Muş-Nemrut-Tendürek volcanoes (Keskin, 2007). Several different geodynamic models were created to explain the collision zone between the Arabian and Eurasian Plates (Şengör and Yılmaz, 1981;Dewey et al, 1986;Barazangi et al, 2006;Keskin, 2007;Zor, 2008;Gök et al, 2011;Skobeltsyn et al, 2014) and many of these were interpreted in detail by Keskin (2007). Şengör et al (2003) revealed that the East Anatolian High Plateau is deprived of mantle lithosphere, which is referred to break-off of northward subducted slab (started some 11 Ma ago) beneath the widespread melting due to direct contact with hot asthenosphere.…”
Section: Geology and Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation